Why and How the Old Neuroleptic Thioridazine Cures the XDR-TB Patient - Joseph Molnar; Leonard Amaral (MDPI AG, 2012)
This mini-review provides the entire experimental history of the development of the old neuroleptic thioridazine (TZ) for therapy of antibiotic resistant pulmonary tuberculosis infections. TZ is effective when used in combination with antibiotics to which the initial Mycobacterium tuberculosis was resistant. Under proper cardiac evaluation procedures, the use of TZ is safe and does not produce known cardiopathy such as prolongation of QT interval. Because TZ is cheap, it should be considered for therapy of XDR and TDR-Mtb patients in economically disadvantaged countries.